THE INFLUENCE OF PROFESSIONALISM, ORGANIZATIONAL CULTURE AND COMPETENCE ON THE PERFORMANCE OF INDONESIAN NAVY SOLDIER AT LANAL PALU - Rahmadi, Rahadian; Natsir, Syahir; Miru, Sulaeman (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aimed to analyze the influence of professionalism, organizational culture and competence on the performance of Navy soldiers at Lanal Palu. This research applied verification type of research with a research population of 108 navy soldiers at the Palu Navy Base where all soldiers are used as research samples through census method. The data analysis technique used multiple linear regression. The results show that the variables of professionalism, organizational culture, and competence simultaneously have positive and significant influence on the performance of soldiers, partially the variables of professionalism, organizational culture, and competence also have positive and significant influence on the performance of the Indonesian Navy soldiers of Palu. The value of the correlation coefficient (R) shows that the close relationship (correlation) of the variables of professionalism, organizational culture, and competence with the performance of Indonesian Navy soldiers of Palu is 93.2% (very strong) with a determinant coefficient value (Adjusted R-Square) of 0.864, meaning that the variable of Soldier performance can be explained by variables of professionalism, organizational culture, and competence of 86.4%. Keywords : Professionalism, Organizational Culture, Competence, Soldier Performance.